Givetian Stringocephalid brachiopods from eastern Yunnan of Southwest China with notes on global distribution of the family Stringocephalidae - Baranov, Valeryi V.; Qiao, Li; Blodgett, Robert B. (Palaeoworld, 2021)
Stringocephalid brachiopods are widely known in the Givetian, but little knowledge is obtained concerning their palaeobiogeographical patterns globally, therefore further studies with new updates and details are required. In this paper, we describe two new stringocephalid brachiopod genera: Yangirostra asiatica n. gen. n. sp. (subfamily Stringocephalinae) and Chinellirostra rara n. gen. n. sp. (subfamily Bornhardtininae), and a new species Stringocephalus sinensis n. sp., together with an indeterminate species Parastringocephalus sp., from the Givetian (late Middle Devonian) of eastern Yunnan, Southwest China. Moreover, with information of the stringocephalides from North Africa, Alaska, North America, Europe and Northeast Eurasia, we compile a dataset of family Stringocephalidae containing 32 genera in 7 subfamilies globally. Based on our data, subfamily Stringocephalinae brachiopods show cosmopolitism and considerably wide distribution from Siberia to the northern Gondwana margins (i.e., North Africa and Australia). Nevertheless, the Boreal Realm and Palaeotethyan Realm are depicted in this paper at the subfamily level, which is much different from the previous palaeobiogeographical schemes in the Givetian. Furthermore, palaeobiogeographical links between Siberia, the Urals and western North America (Alaska, Canada, Nevada and Sonora) are confirmed by diversification of the subfamilies Omoloninae and Rensselandiinae. Whereas in Eurasia (i.e., western and eastern Europe, North and South China), many endemic species of the subfamilies Bornhardtininae and Geranocephalinae are present, as well as the Kaplexinae and Leioseptathyridinae. (C) 2020 Elsevier B.V. and Nanjing Institute of Geology and Palaeontology, CAS. All rights reserved.